Characterization Coal of The Warukin Formation in Kananai Village, South Barito, Central Kalimantan, Indonesia - Arica Nefia; Manek, Emanuel Grace (UIR PRESS, 2026)
This research was conducted to identify geological conditions and the influence of maceral composition on the quality and rank of coal in the study area, which is divided into four rock units. The method used is surface geological mapping to describe the local geological conditions, as well as laboratory analysis which includes maceral analysis, vitrinite reflectance, proximate, and calorific value. The focus of the research is on the unit bedding of mudstone and sandstone with Coal (Warukin Formation) which is a coal-bearing unit. The results of the analysis show that the coal in the study area has the highest rank with an average vitrinite reflectance value (Rv%) of 0.55, the calorific value of 6896 cal/gr, and coal rank is included in the high volatile bituminous C category.